Comparacion de herramientas de software para la coordinacion internacional del roe en la orbita geoestacionaria - Mahecha Galindo, Juan Sebastián; Arévalo Peña, Javier Enrique; Suárez Peñaloza, Martha Liliana; Mantilla Gaviria, Iván Antonio (Visión electrónica, 2016)
This paper presents a comparison of two software tools for technical support in the international frequency coordination of geostationary satellite networks: Visualyse GSO and Sat-Coord. These tools allow the calculation of carrier to noise ratio, carrier to interference ratio, orbital separation arcs and other important parameters described in the radio regulations of the International Telecommunications Union (ITU). In order to better understand the features of these software tools, an overview of the international frequency coordination process for geostationary satellite networks, in planned and non-planned frequency bands is included, as well as general information about the Colombian orbit/Spectrum resource status. The obtained results have been useful for technical studies on coordination of the national Orbit/Spectrum resources, carried out by the Colombian National Spectrum Agency